Quantification is more than counting: Actions required to accurately quantify and report isolated marine microplastics - Rivers, M; Gwinnett, C; Woodall, L (Elsevier, 2018)
Research on marine microplastics continues to increase in popularity, with a large number of studies being published every year. However, with this plethora of research comes the need for a standardised approach to quantification and analysis procedures in order to produce comparative assessments. Using data collected from neuston nets in 2016, parameters for quantifying microplastics were compared. Surface area was the most accurate parameter to describe plastic size and should be used to describe plastic quantity (per km2 or m3), alongside abundance. Of the two most commonly used methods for calculating plastic concentration (flowmeter and ship's log), ship's log provided consistently smaller abundances, with the exception of one sample, calling for a standardisation in the techniques and measurements used to quantify floating microplastics.